Canine presumed glial brain tumours treated with radiotherapy: Is there an inferior outcome in tumours contacting the subventricular zone?. (10th May 2021) - Rohrer Bley, Carla; Staudinger, Chris; Bley, Tim; Marconato, Laura; Sabattini, Silvia; Beckmann, Katrin
Abstract: Post‐treatment outcome in canine glial tumours is described with a broad range of survival times between 2 and 28 months. After surgery or radiation therapy, the tumours may progress locally or spread within the central nervous system. It is unknown if tumour‐ or patient‐specific factors influence prognosis. In humans, glioblastoma involving the subventricular zone has been found to recur distantly, with shortened time to progression and overall survival. We included 32 dogs irradiated for a presumptive primary glial brain tumour in this retrospective cohort study. Tumours were grouped relative to subventricular zone contact and overt ventricular invasion assessing pre‐treatment magnetic resonance images. Median time to progression (TTP) for all cases was 534 days (95%CI, 310–758), with a significantly shorter TTP in dogs with lesions at the subventricular zone (median TTP, 260 vs. 687 days; p  = .049). Tumours at the subventricular zone progressed more often ( p  = .001), and more likely as CNS‐metastasis (52.9% vs. 13.3%, p  = .028). Median overall survival (OS) was 489 days (95%CI, 147–831) and median tumour‐specific survival 609 days (95%CI, 382–835). Involvement of the subventricular zone was significantly associated with a shorter tumour‐specific survival (median, 306 vs. 719 days; p  = .044). Glial tumours contacting the subventricular zone in dogs have a shorter tumour‐specific survival and a higher rate of progression and CNS‐metastasis. Despite local tumour control, metastasis must be considered and should prompt further treatment approaches.